The vaulting table - A new vaulting apparatus in artistic gymnastics - Knoll, Kl.; Krug, J.
Information about the recently FIG-approved new vaulting apparatus, the so-called 'vaulting table'. 1. The new Table is identical for women and men, but with different heights (125cm for female gymnasts and 135cm for male gymnasts). 2. The new Table has an optimal width and length support area ratios for the present vaults, as compared with the previous vaulting horse. 3. The new Table has similar elastic and dynamic characteristics as the previous vaulting horse. This means that gymnasts will need minimal to no adjustments other than the ones related to (the greater) surface area. Practical Implications 1. Overall, the new vaulting table does not demand new push-off techniques from the male gymnasts. 2. The greater, slightly tilted support area offers greater safety and is advantageous to the push-off during all vaults. 3. The longer surface is especially useful for the Yurchenko vaults and its variants performed by female and male gymnasts. 4. The female gymnasts will benefited by the longer surface for all vaults compared to the old vaulting horse that was cross-placed. 5. The push-off for women's Tsukahara will approximate the male technique.